Effect of arsenic and cyanobacterial co-exposure on pathological, haematological and immunological parameters of rainbow trout (Oncorhynchus mykiss) - Palikova, Miroslava; Papezikova, Ivana; Kopp, Radovan; Mares, Jan; Markova, Zdenka; Navratil, Stanislav; Adamovský, Ondřej; Kohoutek, Jiří; Navratil, Lukas; Blaha, Ludek (Neuro-endocrinology letters, 2015)
OBJECTIVES: Under environmental conditions, fish are simultaneously exposed to multiple stressors. This study provides new knowledge on the effects of controlled exposure to multiple stressors, namely cyanobacterial biomass and food contaminated with arsenic. METHODS: Rainbow trout were divided into six groups of 25 fish and exposed to different contaminant combinations for 30 days: 1) control group, 2) cyanobacterial biomass, 3 & 4) two groups exposed to arsenic at concentrations of 5 mg.kg(-1) and 50 mg.kg(-1) fish feed, and 5 & 6) two groups exposed to cyanobacterial biomass and arsenic combined. We then evaluated pathological, haematological and immunological parameters at 10, 20 and 30 days after exposure. RESULTS: Marked gross pathological findings were present in groups exposed to arsenic and arsenic/cyanobacteria after 30 days. A strong decrease in haemoglobin concentration was observed in all experimental groups receiving arsenic after 10 days exposure. Total leukocyte count increased markedly in fish exposed to cyanobacterial biomass, and to higher arsenic concentrations by the end of the experiment. Neutrophils decreased significantly at the end of exposure. Similarly, exposure to cyanobacteria and/or arsenic led to suppression of opsonised zymosan particle-induced neutrophil respiratory bursts. CONCLUSIONS: Our results demonstrate that the effects of exposure to toxic cyanobacterial biomass and arsenic on fish are enhanced when the contaminants are combined. In particular, long-term exposure led to disturbances in the white blood-cell count. Modulation of phagocytosis, which is the first line of defence against invading pathogens, suggests that the combined action leads to a decreased ability to control infection.
Keywords: Animals; mikrocystiny; Iron; Arsenic; zvířata; Microcystins; arsen; Bacterial Infections; Phagocytes; Erythrocyte Indices; karcinogeny; fagocyty; Carcinogens; Microcystis; železo; počet leukocytů; Neutrophils; bakteriální infekce; erytrocytární znaky; Oncorhynchus mykiss; Leukocyte Count; Cyanobacteria; sinice; neutrofily